2019
DOI: 10.7717/peerj.8278
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characteristics of non-familial epilepsy

Abstract: BackgroundKnowledge of the genetic etiology of epilepsy can provide essential prognostic information and influence decisions regarding treatment and management, leading us into the era of precision medicine. However, the genetic basis underlying epileptogenesis or epilepsy pharmacoresistance is not well-understood, particularly in non-familial epilepsies with heterogeneous phenotypes that last until or start in adulthood.MethodsWe sought to determine the contribution of known epilepsy-associated genes (EAGs) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…These findings are consistent with previous literature that reported on the diagnostic yield in the absence of a positive family history of epilepsy and the overall high de novo rates for many of these genes. 24 , 33 These data suggest that individuals with epilepsy of unexplained cause presenting at any age and with ID/DD comorbidities, regardless of family history, often have an identifiable genetic diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are consistent with previous literature that reported on the diagnostic yield in the absence of a positive family history of epilepsy and the overall high de novo rates for many of these genes. 24 , 33 These data suggest that individuals with epilepsy of unexplained cause presenting at any age and with ID/DD comorbidities, regardless of family history, often have an identifiable genetic diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…According to the EpilepsyGene database ( http://www.wzgenomics.cn/EpilepsyGene/index.php ), ~500 genes may be associated with epilepsy, and ~2% of idiopathic epilepsy patients are thought to be monogenic (Ran et al, 2015 ). Mutations in Sodium Voltage-Gated Channel Alpha Subunit 1 ( SCN1A ), Potassium Voltage-Gated Channel Subfamily Q Member 2 ( KCNQ2 ), Cyclin Dependent Kinase Like 5 ( CDKL5 ), Protocadherin 19 ( PCDH19 ), and Proline Rich Transmembrane Protein 2 ( PRRT2 ) were the most common genetic lesions of epilepsy (Wang J. et al, 2017 ; Kang et al, 2019 ). In addition, recent studies revealed that epilepsy may be a presenting and prominent symptom of ChAc caused by VPS13A mutations (Benninger et al, 2016 ; Weber et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic Characteristics In Drug-resistant Epilepsy Of Published Studies Table 3 provides a summary of previous studies about genetic characteristics in DRE [12][13][14][15][16][17][18][19][20][21]. Regardless of varied molecular diagnostic tool used between studies, some gene mutations were found to appear repeatedly, such as SCN1A (5.6%, n = 74/1308), followed by SCN8A (1.37%, n = 18/1308), TSC2 (1.22%, n = 16/1308), SCN2A (1.07%, n = 14/1308) and KCNQ2 (0.99%, n = 13/1308) 3).…”
Section: Discussionmentioning
confidence: 99%